(3hab YOO ef GdQDi aj GdacQ GdEOGQjs - (3GeMeO(B, (3JbGQs ((3GdLRGFQ(B:s (3OGQ EjdjGA ddfTQ hGdJhRjY(B,s, 2024)
(3EOGQI GdeYQaI aj GdefXhQ GdbGFe Ydi GdehGQO, EOGQI GdeYQaI aj GdefXhQ GdbGFe Ydi GdeYQaI, EOGQI GdeYQaI ef efXhQ GdKbGaI GdJfXjejI, EOGQI GdeYQaI aj GdefXhQ GdJaGYdj Ch GdOjfGejcj, s
(3HHdjhZQGajG(B: (3U(B.(3U(B113-119s
Keywords: (3EOGQI GdeYQaIs; (3GdeYQaIs